Capital Structure Decisions and Corporate Performance: Evidence from Chinese Listed Industrial Firms. - Vijayakumaran, R. (International Journal of Accounting and Financial Reporting, 2017)
Market imperfections such as taxes, asymmetric information and agency problems make capital structure decisions relevant to the value of the firm. More specially, the agency theory suggests that debt financing is one of the governance mechanisms to mitigate agency costs of equity capital and thus to enhance firm performance. This paper provides new empirical evidence on the performance effects of capital structure decisions using a large panel of Chinese listed industrial firms. Using fixed effects regression method, the study finds that leverage is positively related to firm performance, suggesting that debt financing now acts as a governance mechanism for Chinese listed firms to enhance their performance.
Keywords: Capital structure; Agency problem